Stress-Induced Cardiomyopathy - Ronderos, Ricardo E. (2009)
Stress-induced cardiomyopathy is a relatively uncommon syndrome with difficult definition. Cases with transient and reversible left ventricular dysfunction, precipitated by emotional stress and without coronary artery disease, are called takotsubo syndrome, left ventricular apical ballooning, and broken heart syndrome. Many names used to refer to this syndrome are related to the shape of the left ventricle and/or the precipitating factors, but there is not yet a consensus about the proper name. Situations related to physical stress, such as intracranial bleeding, have similar patterns, including the absence of previous cardiac involvement. The increased blood levels of endogenous catecholamine, and increase of myocardial catecholamine in areas with high density of sympathetic innervations, seem to be the mechanisms for myocardial cell necrosis with eosinophilic transverse bands. The localized spasm of the epicardial coronaries, or diffuse microcirculatory dysfunction, is also one of the proposed mechanisms. There are still some areas of controversy that have no definite answer.